RESTOS DE UN PROTOHYDROCHOERINAE (RODENTIA, HIDROCHOERIDAE) EN EL "MESOPOTAMIENSE" (PLIOCENO MEDIO-TARDIO) DE LAS BARRANCAS DEL RIO PARANA (PROVINCIA DE ENTRE RIOS, ARGENTINA) (Ameghiniana, 2013)
Cheek-teeth fragments of a extinct capybara's subfamily, Protohydrochoerinae, are C:escribed. This is the first record of this taxon in the Pliocene "Mesopotarnian" levels from the Paraná river clifts. They are compared with those recorded in the southern area during the Later Pliocene (Montehermosan Land-Mammal Age ), as are both environmental conditions. The environmental conditions, as well as the different relative age, are considered as the causes of the more frequent record of the Protohydrochoerinae in the more typical southern pampean area.